Liquid smoke-infused edible coatings: Antimicrobial agents for preserving cherry tomatoes - Muhammad Faisal; Dieni Mansur; Hera Desvita; M. Bagas Heriansyah (Case Studies in Chemical and Environmental Engineering)
This study aimed to explore the effectiveness of edible coating to extend the shelf life of cherry tomato at room temperature. The edible coating was made from a mixture of liquid smoke with a concentration of 2–6% v/v (pyrolysis of rice husks (Oriza sativa) and cajuput (Melaleuca leucadendron) twigs) at a temperature of 500 °C), 0.5 % gelatin, 4 % chitosan, 1.5 % CMC (Carboxymethyl Cellulose), and distilled water. All ingredients were mixed into a homogeneous solution and cherry tomato was soaked for 15 minutes in the edible coating solution. The effectiveness of edible coating was tested based on antibacterial activity against 4 types of pathogenic bacteria, namely Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis, as well as 2 fungi including Candida albicans and Aspergillus niger. The quality of cherry tomato was also analyzed through the Most Probable Number (MPN) test for E. coli and the measurement of the L∗ value. The results showed that edible coating was effective in inhibiting the growth of pathogenic microbes and could maintain the freshness of cherry tomato for approximately 15 days of storage at room temperature in sample RK3 as well as 9 days in SP2 and SP3 (liquid smoke from rice husks). Furthermore, changes in L∗ values significantly reduced in cherry tomato during storage. These results showed that edible coating can prevent the decline in the quality of cherry tomato during storage at room temperature.